Peningkatan Minat Belajar IPAS Berbantuan Media Gambar Pada Siswa Sekolah Dasar - Komang Surya Adnyana; Gusti Ngurah Arya Yudaparmita (STAHN Mpu Kuturan Singaraja, 2023)
Interest in learning is an interest possessed by students which can be expressed as a statement indicating that students prefer something over other things, manifested through participation in an activity. Students who have an interest in certain subjects tend to pay greater attention to certain subjects. Social Knowledge learning media in elementary schools, especially in image media, is a tool that can be used to deliver or convey messages in the form of knowledge to students so that learning objectives can be achieved. Indicators of interest in learning in this study include: 1) paying attention to the teaching and learning process, 2) having a liking for lessons, 3) enthusiastic students, 4) enthusiastic in learning, 5) having active learning